Preparation and Properties of Non-Crosslinked and Ionically Crosslinked Chitosan/Agar Blended Hydrogel Films - Mohamed Mahmoud Nasef; Esam A. El-Hefian; Sariah Saalah; Adul Hamid Yahaya (E-Journal of Chemistry)
Hydrogel films of chitosan (Cs) and agar blends of various proportions were prepared using physical solution blending. Some of the obtained films were ionically cross-linked by treatment with calcium chloride solution. The obtained films were characterized by Fourier transform infrared (FTIR) spectroscopy, thermogravimetry analysis (TGA), differential scanning calorimetery (DSC) and universal mechanical tester. The non-crosslinked Cs/agar blended films showed lower water swelling, melting temperature, stiffer and less elastic properties than that of pure Cs films and higher than pure agar films. Crosslinked blended films displayed further reduction in the swelling and melting temperature while maintained more hydrogel stability.